Peran Relawan Pajak Dalam Upaya Meningkatkan Pelayanan Perpajakan Di Kantor Pelayanan Pajak Pratama Bekasi Barat - Nugraha, Ryan; Wijaya, Teguh; Harjo, Dwikora (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Tax services play a crucial role in influencing taxpayer satisfaction. However, the service provided by the tax authorities at the West Bekasi Pratama Tax Service Office has not reached its maximum potential, resulting in suboptimal levels of taxpayer satisfaction. To address the issue, the Directorate General of Taxes (DJP) collaborates with Tax Centers in various universities, including the Tax Center at STIAMI Institute, through the Tax Volunteer Program. This study aims to analyze the role of tax volunteers in enhancing tax services at the West Bekasi Pratama Tax Service Office and identify the obstacles and solutions in the tax volunteer assistance. The theoretical framework used is Levinson’s theory of roles. The research method employed is a qualitative approach, specifically descriptive research. The data used in this study consists of primary data obtained through informant interviews, as well as secondary data. Data collection techniques include interviews, observations, and documentation. The findings of the study indicate that the role of tax volunteers in improving tax services is quite optimal, as taxpayers express satisfaction with the assistance provided by tax volunteers in completing their Annual Individual Tax Returns (SPT). As a result, taxpayer satisfaction with the services has increased to 91.11%. However, several obstacles exist in the implementation of the tax volunteer program, including conflicting schedules, insufficient taxpayer knowledge, some tax volunteers lacking competence, limited human resources for EFIN creation, absence of queue numbers, and occasional server downtime.